Macroeconomic Differentials and Adjustment in the Euro Area - Iulia Siedschlag (SUERF - The European Money and Finance Forum, 2008)
There has recently been increased research and policy interest in the divergent macroeconomic performance in the European Economic and Monetary Union (EMU). Understanding the underlying factors of macroeconomic differentials, the source and transmission of shocks and the adjustment process in the euro area is important to appropriate economic policy in the EMU. In a monetary union, the single monetary policy can only address common shocks. In the absence of nominal interest and exchange rates as policy instruments, to adjust to asymmetric shocks ? country specific shocks or idiosyncratic effects of common shocks, member countries have to resort to remaining tools of economic policy. In theory, the adjustment to asymmetric shocks and return to equilibrium can take place through four channels: a) market ? driven price and output adjustment; b) policy induced fiscal adjustment; c) risk-sharing against country-specific shocks through fiscal transfers and financial integration; d) labour mobility. Temporary inflation and output growth differentials are likely in a common currency area since prices and output adjustment is required to absorb shocks. In the euro area, output growth and inflation differentials are also related to the ongoing catch - up process in some of the member countries. Persistent inflation differentials can have negative effects on incomes and investment and result in divergent competitiveness and monetary conditions in the participating countries. Furthermore, inappropriate use of national fiscal policy and real exchange rate adjustment can lead to poor macroeconomic performance. The objective of this paper is to analyse macroeconomic differentials and the adjustment in the euro area so far with the aim to draw lessons and policy implications for the better functioning of the EMU and euro areaenlargement. The questions we address are the following: What do we know about macroeconomic differentials in the euro area? Are they temporary or persistent? What factors underlie them? What is the likelihood of asymmetric shocks in the euro area and what are their main transmission channels? What policy issues related to the macroeconomic adjustment in the EMU are most important at this stage? The remainder of this study is organised as follows. In Section 2 we analyse the size, evolution, persistence and underlying factors of output growth and inflation differentials. Section 3 discusses the likelihood of asymmetric shocks and their transmission across the euro area countries. In particular, we analyse trade linkages, including intra- and extra-euro area trade, financial integration and business cycle synchronisation. In Section 4 we discuss a number of policy issues related to the macroeconomic adjustment in EMU which have gained increased interest recently. We start with the role and effects of real interest rate and competitiveness differentials as adjustment channels. We discuss next policy issues related to fiscal adjustment and the impact of fiscal shocks in the euro area countries. We then discuss labour mobility as an adjustment mechanism. Finally, Section 5 summarises the main findings and draws policy implications for the EMU and the euro area enlargement.
Keywords: E32; E44; F41; 330; European Economic and Monetary Union; International transmission of shocks; Macroeconomic adjustment; Eurozone; Schock; Wirtschaftswachstum; Wirtschaftliche Anpassung; EU-Staaten